2017
DOI: 10.1002/macp.201600547
|View full text |Cite
|
Sign up to set email alerts
|

STED Analysis of Droplet Deformation during Emulsion Electrospinning

Abstract: The shape and size distribution of polystyrene (PS) compartments formed during emulsion electrospinning in a poly(vinyl alcohol) fiber is investigated. Stimulated emission depletion microscopy is employed to image the compartments with subdiffraction (super) resolution. The size distribution of the emulsion droplets in the spinning solution emulsions is found to be the key factor for fiber and compartment morphology. By varying the emulsification method, it is demonstrated that fibers spun from miniemulsions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Therefore, upon mixing of two different stable miniemulsions with the same continuous phase and the same surfactant, no significant mass transfer from the different droplets occurs . Conversely, when miniemulsions are electrospun, they experience stretching in the polymer jet that may lead to coalescence, depending on the electrospinning conditions and on the viscosity mismatch between the dispersed and continuous phases . In the second process, fibers were spun by the so‐called side‐by‐side electrospinning process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, upon mixing of two different stable miniemulsions with the same continuous phase and the same surfactant, no significant mass transfer from the different droplets occurs . Conversely, when miniemulsions are electrospun, they experience stretching in the polymer jet that may lead to coalescence, depending on the electrospinning conditions and on the viscosity mismatch between the dispersed and continuous phases . In the second process, fibers were spun by the so‐called side‐by‐side electrospinning process.…”
Section: Resultsmentioning
confidence: 99%
“…The visualization of rather thick hydrogel constructs composed of nanofibers with diameters ranging between 80 and 100 nm highlights the power of SRM material imaging. On the contrary, the analysis of electrospun fiber with SRM is still rather scarce. Friedemann et al demonstrated the potential use of SRM on the characterization of electrospun fibers . Using STED-based SRM, the authors visualized the distribution of PS nanoparticles with the radii down to ∼50 nm on a few hundred nanometers wide PVA nanofibers.…”
Section: Emerging Techniques For the Surface-sensitive Characterizationmentioning
confidence: 99%
“…The visualization, with the above described methods, of apolar structures found in material science is often impossible since the employed polar switching buffers cannot significantly access apolar structures, whereas fluorescent proteins, if appropriate to be used, would denature under such conditions. As a consequence, super‐resolution microscopy has so far not been used extensively to address topics in soft matter or polymer science …”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, superresolution microscopy has so far not been used extensively to address topics in soft matter or polymer science. [25][26][27][28][29][30][31][32][33][34][35] Universal application of SRI in the field of material sci ence mostly depends on the availability of switchable dyes with suitable photophysical and chemical properties such as high fluorescence quantum yield, large separation between the absorption bands of the on and offstate, high photostability, adjustable switching kinetics, minimum interaction with the environment, and a straightforward derivatization approach for specific structure labeling.…”
Section: Introductionmentioning
confidence: 99%